Frequency of classes I and II HLA alleles in deceased donors of solid organs in Espírito Santo, Brazil - Fabiana Regina Barbosa; Karla O. Freitas; Rafaela C. Silva; Sarah P. C. Pires; Rodrigo Pratte-Santos (Sociedade Brasileira de Patologia Clínica, 2017)
ABSTRACT Introduction: The Brazilian population has a great racial mix, originating mainly from Europeans, Africans and Indians. Human leukocyte antigens (HLA) specificities vary among different population and ethnic groups, since they demonstrate greater similarity in populations of common origin. Objective: To determine the genetic structure of HLA classes I and II alleles in deceased donors of solid organs in the state of Espírito Santo, Brazil, from 2011 to 2015. Methods: The present study covered 208 brain-dead donors of solid organs, from 2011 to 2015, in the state of Espírito Santo, Brazil. HLA typing was performed by polymerase chain reaction-sequence specific oligonucleotide probes (PCR-SSP) using kits for generic classes I and II SSP DNA typing test, A, B and DR loci. Results: The profile of deceased donors found in Espírito Santo, Brazil, in the period from 2011 to 2015, was brown men, aged over 40 years. The most frequent HLA alleles were A2 (24.28%), B44 (10.34%) and DR15 (14.18%); and the least frequent, A43 (0.24%), B46, B47, B70, B75 and B78 (0.24%) and DR9 (1.68%), DR12 and DR18 (2.16%). Conclusion: The present study contributed with significant information about the frequency of HLA antigens in deceased donors of solid organs in the Brazilian population that will contribute to optimize the transplantation process in the country.